Analysis of Factors Influencing Customers' Decision to Choose Wadiah Savings Products - Fakziah, Sefia Laili; Clarashinta Canggih (Indonesian Journal of Economic & Management Sciences, 2024)
This study aims to analyze product knowledge, benefit perception, promotion, and motivation factors as factors in customers' decision to choose wadiah savings products at Sharia Banks. The background of this research is the growth of the Islamic banking industry in Indonesia, which is predicted to be higher than conventional banks, driven by product and service innovation in accordance with Islamic law. This study uses a quantitative approach with confirmatory factor analysis (CFA) techniques. Research data was collected through a questionnaire with a probability sampling method using a simple random sampling technique. The results of the study show that promotional factors, product knowledge, and benefit perception are factors in customer decisions in choosing wadiah savings products. The motivation factor is not a factor in the customer's decision to choose a wadiah savings product. This research provides insight into the importance of proper promotion, in-depth product knowledge, and clear benefit perception in attracting customers to choose wadiah savings products at Sharia Banks